The Guestbooks of Antanas Baranauskas’s Granary – a Source for Researching Lithuania’s Cultural History - Liepaitė, Inga (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] In Anykščiai, in a memorial museum dedicated to the heritage of Antanas Baranauskas and Antanas Vienuolis-Žukauskas, kept are six guestbooks of Antanas Baranauskas’s granary. Antanas Baranauskas (1835–1902) – Lithuanian poet, linguist, mathematician, translator, suffragan of the Samogitian Diocese and bishop of Seinai. These guestbooks were filled out during the period when the granary was being maintained, looked after and managed by the writer Antanas VienuolisŽukauskas (1882–1957), grandson of Jonas Baranauskas (1828–1904), Antanas Baranauskas’s brother. Using published and unpublished materials, four principal aims were tackled by this article: 1) To reveal how A. Vienuolis-Žukauskas came up with the idea of A. Baranauskas’s granary guestbooks and how was that idea eventually realized; 2) To discuss the contingent of the visitors of Lithuania’s first memorial museum; 3) To describe the guestbooks of A. Baranauskas’s granary as a source for researching the history of the development of the Museum and Lithuania’s museology; 4) To determine whether the guestbooks of A. Baranauskas’s granary ought to be ascribed to the category of egodocuments. The study has led us to the conclusion that the heritage objects of the described genre haven’t thus far received enough attention in Lithuania. Books that were being consistently filled out by guests or visitors of one or another institution could become important auxiliary sources for both researching the history of a specific institution and revealing the wider cultural context of a given period. Also, texts of this genre possess some elements of the autobiographical narrative. The foundational typology of egodocuments ought to be expanded with an additional component – the books of visitors or guests of institutions. This provision should add relevance to studying the heritage objects of the described genre. More numerous and more varied studies, as well as comparative ones, would provide the means for further discussions.